Efeito da varicocele e de sua correção cirúrgica nos mecanismos moleculares proteômicos e inflamatórios do sêmen - Camargo, Mariana [UNIFESP] (2016)
Introduction: Varicocele is the main treatable cause of male infertility. On the other hand, not all men with varicocele will be infertile. There are several proposed mechanisms to explain varicocele-derived infertility, among them, an increase in seminal inflammatory activity. One of the main therapeutic options for men with varicocele is varicocelectomy, which presents a success rate of 50-80%, measured by an increase in seminal quality. Thus, it is important to verify which patients have the best potential for a positive outcome after varicocelectomy. Objective: This study was divided into two different studies. The aims of study 1 were: (i) to verify if seminal plasma of men with varicocele presents inflammasome complex-derived inflammatory activity; and (ii) to verify if surgical correction of varicocele alters seminal levels of inflammasome complex proteins. The aims of study 2 were: (i) to observe the effect of varicocelectomy in the seminal plasma proteomic profile of adult men; and (ii) to verify if the seminal plasma proteome is able to identify which patients will present seminal parameters improved after varicocelectomy. Methods: In study 1, 15 men without varicocele (control group) and 15 men with varicocele, with indication for surgery, were included. Control men performed one semen collection, and varicocele men performed two semen collections: one before varicocelectomy, and another 6 months after the surgery. In both groups, evaluation of sperm quality, functional sperm analysis, semen lipid peroxidation and inflammasome proteins analysis were performed. In study 2, 25 men with varicocele, who underwent varicocelectomy, were included. Semen collection was performed before and 1 year after varicocelectomy, and then proteomic analysis was carried out. Also, for another proteomic analysis, the pre-surgical samples were divided into two groups: group 1 ? patients who underwent varicocelectomy but did not have any of the seminal parameters improved and, group 2 ? patients who underwent varicocelectomy and obtained seminal parameters improvement. Results: Study 1 verified that varicocele led to increased seminal plasma levels of IL-1?, and varicocelectomy decreased seminal plasma levels of IL-18, IL-1? and caspase-1. In study 2, enriched functíons demonstrated the presence of cell death induced by oxidative stress in patients with varicocele, and that varicocelectomy enrich functíons such as cell motility and serine endopeptidase activity. Furthermore, TPP1 protein is able to predict a positive outcome of varicocelectomy, with an area under a ROC curve of 84.5%. Conclusion: Based on our results, we can conclude that: (i) seminal plasma of men with varicocele presents inflammasome-derived inflammatory activity; (ii) varicocelectomy improves testicular function and decreases seminal levels of inflammatory complex cytokines; (iii) varicocelectomy decreased cell death induced by oxidative stress activity and proteasome degradation, and can enrich cell migration and serine endopeptidase functions; and (iv) TPP1 protein is able to predict positive outcome in men who will undergo varicocelectomy.